Pengaruh Kompetensi Terhadap Disiplin Kerja Pegawai Di Dinas Kependudukan Dan Catatan Sipil Kabupaten Enrekang - Syamsidar, Syamsidar; Hakim, Lukman; Malik, Ihyani (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aims to determine the effect of competence on work discipline in the department of population in enrekang district. This type of research is a quantitative approach, the population of this study is all employees of the department of the department of population and civil registration Enrekang district, amounting to 50 people data collected by a questionnaire that has been tested for reliability thr data analysis techique used is multiple regression results the rearch shows that the competency of employees in the departement of population and civil registration of Enrekang regency is based on the results of data from the analysis of competency variables (X)shows that getting into the category of good things can be seen from the indicators used ie work experience is at a percentage level of 90%, work discipline based on the results of data analysis the work discipline variabele (Y) shows that the work discipline of its employees falls employees falls into the good categoryare in the goog category seen from the indicators with the level of achievement that is with a timeline 80% work discipline increased by 0,664. The coefficient is positive, so it can be said that the direction of the influence of variabeles X with Y is positive.